Influence of technological parameters of centrifugal reinforcement upon quality indicators of parts - Роп’як, Любомир Ярославович; Шуляр, Ірина Орестівна; Богаченко, Олег Михайлович (Eastern-European Journal of Enterprise Technologies, 2016)
Analysis of surface and three-dimensional reinforcement methods to enhance the wear-resistance of parts is performed. The advantages of centrifugal reinforcement of the part blanks with two mutually perpendicular axes of rotation of the ceramic mold to produce the reinforced zone with desired properties are substantiated. The influence of technological parameters of centrifugal reinforcement of steel parts with tungsten carbide particles in the casting process on the concentration and the wear of the working area using the mathematical experimental design is investigated. Second-order regression models for dependencies of concentration and wear on the technological process parameters: the number of rotations around the horizontal and vertical axes of the ceramic mold, heating temperature of the ceramic mold and heating temperature of reinforcing tungsten carbide particles are built. The optimum values of frequencies of rotation around the horizontal and vertical axes, heating temperatures of the mold and reinforcing particles, which provide the maximum concentration of tungsten carbide particles in the working area and minimum wear are determined. It is found that the concentration of tungsten carbide particles in the working area and wear are affected by the kinematic components of technological parameters more than temperature ones. For centrifugal reinforcement of inserted drilling bit teeth with 1.0 mm tungsten carbide particles with two mutually perpendicular axes of rotation of the ceramic mold, the following technological parameters are optimal: nx=217 rpm; nz=702 rpm; Tф=270 oC; Ta=208 oC providing a maximum tungsten carbide concentration in the working area and minimum wear. The research results are useful in the development of technological processes of manufacturing turned parts with the reinforced working area, namely disc and tooth rolling cutters, milling cutters, blade drilling bits, inserted drilling bit teeth.